Tailoring the corrosion behavior and mechanism of Mg-Gd-Zn alloys via Sc microalloying - Jun Wang; Yingying Li; Yuan Yuan; Li Yang; Liang Wu; Fuyong Cao; Ligang Zhang; Andrej Atrens; Xianhua Chen; Fusheng Pan (Journal of Materials Research and Technology, 2023)
The Sc microalloying can decrease the corrosion rates of Mg-Gd-Zn alloys by about two orders of magnitude, and thus significantly improving corrosion resistance of Mg-Gd-Zn alloys. Notably, the Sc microalloying can inhibit the precipitation of (Mg, Zn)3Gd phase with high potential while promote the precipitation of 14H-LPSO phase with low potential under the premise of reducing the total amount of second phases. Thus, the micro-galvanic corrosion effect can be effectively weakened. Additionally, the Sc microalloying can lead to the grain refinement, which can act as barriers to corrosion propagation and promote the nucleation and growth of oxides. Also, the activity of Gd, Zn and Sc in α-Mg phase can be increased with the Sc microalloying, which facilitates the formation of related continuous and compact oxide films. The continuous and compact films can effectively protect the alloy matrix from corrosion. Furthermore, the stacking faults distributed in different grains with different orientations in Sc-contained alloys can lead to a more uniform corrosion. The synergistic effects resulted by Sc microalloying contribute to the significantly improved corrosion resistance of Mg-Gd-Zn alloys.